EFEKTIVITAS PEMBERDAYAAN MASYARAKAT DALAM PELESTARIAN HUTAN MANGROVE DI DESA KUALA SATONG - Roslinda, Emi; Rahmah, Adhea Nuur; Hardiansyah, Gusti (JURNAL HUTAN LESTARI, 2025)
Community empowerment is an effort that local communities can undertake to preserve mangrove forests. Community empowerment in Kuala Satong Village is already underway; however, it is essential to note that this empowerment has yet to achieve its goal. Therefore, it is necessary to assess the effectiveness of community empowerment in efforts to preserve mangrove forests. This research objective to describe the level of effectiveness of community empowerment in preserving mangrove forests in Kuala Satong Village. The research method employed is a survey method with a purposive sampling technique, utilizing a questionnaire administered to respondents. The data are then analyzed descriptively, qualitatively, and quantitatively. The research results indicate that the effectiveness of community empowerment in mangrove forest conservation efforts falls within the 'effective enough' category. This is evident in the Community Empowerment Effectiveness variable, which comprises three indicators: Achievement, Adaptation, and Integration. Effectiveness assessment is also supported by the Conservation Effort variable (Physical) and the Conservation Effort variable (Non-Physical). Keywords: community empowerment, effectiveness, mangrove, preservation, Abstract Pemberdayaan masyarakat merupakan upaya yang penting untuk melestarikan hutan mangrove di lingkungan setempat. Di Desa Kuala Satong, pemberdayaan masyarakat telah dilakukan, namun perlu dilakukan penilaian guna mengetahui sejauh mana pemberdayaan tersebut telah mencapai tujuannya. Penelitian ini bertujuan untuk mendeskripsikan tingkat efektivitas pemberdayaan masyarakat dalam pelestarian hutan mangrove di Desa Kuala Satong. Metode yang digunakan adalah survei dengan teknik pengambilan sampel purposive sampling dan pengumpulan data melalui kuesioner yang diberikan kepada responden. Data kemudian dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa efektivitas pemberdayaan masyarakat dalam pelestarian hutan mangrove termasuk kategori cukup efektif. Hal ini berdasarkan tiga indikator utama efektivitas pemberdayaan masyarakat, yaitu pencapaian, adaptasi, dan integrasi. Penilaian efektivitas ini juga didukung oleh variabel upaya pelestarian fisik dan non-fisik. Kata kunci : Pemberdayaan Masyarakat, Efektivitas, Mangrove, Pelestarian